Identifikasi Cendawan Rhizosfer Tanaman Jagung (Zea Mays L.) dan Uji Efektivitas Media Perbanyakan Trichoderma sp. - Widiati, Bibiana Rini; Herwati, Andi; Sofyan, S (Journal Galung Tropika, 2022)
Utilization of local microorganisms is important to utilize the potential of the area by utilizing tea waste as a mixture of new alternative culture media for the propagation of Trichoderma sp. The aim of this study was to identify locally specific rhizosphere fungi and determine the appropriate media mix for the propagation of Trichoderma sp. The research consisted of 2 stages. The first stage used a descriptive-exploratory method by taking random soil samples in Kab. Pangkep, Maros, and Gowa on the rhizosphere of maize cultivation. The second stage used a factorial design in RAL (Completely Randomized Design) which consisted of two treatment factors, namely: Factor I. Administration of the fungus Trichoderma sp. (C), c1 = Trichoderma sp. from Pangkep, c2 = Trichoderma sp. from Goa. While factor II is the growing medium (M), m1 = 200 g rice, m2 = 150 g rice + 50 g tea waste, m3 = 100 g rice + 100 g tea waste, m4 = 50 g rice + 150 g tea waste, m5 = tea dregs 200 g, There were 10 treatment combinations, each treatment combination was repeated 3 times so that there were 30 experimental units in total. The results of the study showed that 8 fungi isolates were obtained from the rhizosphere fungi from corn from Pangkep, Maros, and Gowa. Fungus isolates from Pangkep Regency 3 isolates (Trichoderma sp, black Aspergillus sp, green Aspergillus sp), Maros Regency 2 isolates (black Aspergillus sp, Verticellium sp), and Gowa Regency 3 isolates (Trichoderma sp, green Aspergillus sp, Verticellium sp ). The medium of 150 g of rice + 50 g of tea dregs is the best medium for the multiplication of Trichoderma sp. resulting in a higher width, length, and density of conidia than other treatments.